ANALISIS KEPUASAN MASYARAKAT DALAM PELAYANAN IJIN TRAYEK DAN KIR PADA DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMASI KOTA SERANG - Arenawati Arenawati; Listyaningsih Listyaningsih (Universitas Sultan Ageng Tirtayasa, 2016)
Route Permit Services and KIR are the two most important services is the taskof the Department of Transportation, Communication and Information. KIR trajectorylicense and is a prerequisite that must be owned by a transport vehicle, both of freightand human transport. The public, especially those who have public transport and goodswill be dealing with related services and KIR publishing trajectory license or Certificateis roadworthy vehicle. This research uses descriptive quantitative method. Thepopulation in this study were people who did KIR.Hasil trajectory license and researchshows that the value of people's satisfaction in service and KIR trajectory license at theDepartment of Transportation, Communication and Information Serang City is at 73.25categorized as good. Suggestion of this research is to multiply the seat in the waitingroom, replacing KIR test equipment with the modern tools.